2013
DOI: 10.1007/s10561-013-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mesenchymal stem cells derived from fetal bovine liver

Abstract: Bovine liver-derived mesenchymal stem cells (bLMSCs) were isolated from the liver tissue of 4-6 months old fetal calf, and then characterized by immunofluorescence and RT-PCR. We found that primary bLMSCs could be subcultured to 44 passages, the total culture time in vitro was 192 days. The results of surface antigen detection showed that bBMSCs expressed CD29, CD44, CD73, CD90, CD106 and CD166 but not expressed endothelial cells and hematopoietic cells specific marker CD34, CD45 and BLA-DR. The results of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In-depth analysis has been performed for BMSCs (4,5), which exist in a wide range of tissues (6)(7)(8). Many researchers (6,8,9) believe that MSCs originate from adult stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth analysis has been performed for BMSCs (4,5), which exist in a wide range of tissues (6)(7)(8). Many researchers (6,8,9) believe that MSCs originate from adult stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, all encompass characteristics of multilineage differentiation potential [24,25]. Lu et al [8] have reported the isolation and characterization of MSCs that were derived from a fetal bovine liver (LMSCs) in their study. These bovine LMSCs could be subcultured for up to 44 passages, and expressed CD29, CD44, CD73, CD90, CD106, and CD166 but not CD34, CD45, and BLA-DR. Further, bovine LMSCs exhibited substantial proliferating ability and mesodermal differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have sought to establish bovine MSCs from various tissues. To date, bovine MSCs have been isolated from bone marrow [6], umbilical cord blood [7], amniotic fluid [1], liver [8], adipose tissue [9], endometrial tissue [10], and Wharton's jelly [11]. The objective of the present study was to isolate MSCs from bovine tongue tissues, and to fully characterize bovine tongue tissue epithelium-derived MSCs (boT-MSCs) by analyzing cell growth curves, cell surface markers, and stemness such as the mesodermal differentiation potential of Korean native cattle.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs may be isolated from various sources, including umbilical cord (UC), bone marrow (BM), liver, adipose tissue, multiple dental tissues and induced pluripotent stem cells (28,29). MSCs express CD44, CD73, CD90 and CD105, but not CD45, CD34 and CD14; these cells are characterized by their ability to adhere to plastics under standard cell culture conditions (30).…”
Section: Stem Cellsmentioning
confidence: 99%